Kualitas Hubungan dan Brand Experience: Pengaruhnya terhadap Kepuasan Pelayanan Administrasi Rumah Sakit di Kota Pontianak - Dewi Santika (MABIS, 2022)
This research is intended to see the influence of relationship quality and brand experience on the administration service satisfaction at 11 hospitals in Pontianak. Analysis instruments used multiple linear regression with the sampling technique used quota sampling and the sampling method used accidental sampling. Result of this research indicated that the relevancy of relationship quality and brand experience has positive and significant effect on the administration service satisfaction at hospitals in Pontianak as well as simultant also partial.Keywords:     relationship quality, brand experience, and administration service satisfaction.